Faktor Penentu Capaian Sains Siswa Indonesia: analisis multilevel pada dataset PISA - Tia Asri Ivanka; Ezra Putranda Setiawan (Jurnal Penelitian Pendidikan IPA, 2025)
Students' science achievement is one indicator of a country's progress in science and technology. Until 2022, the Programme for International Student Assessment (PISA) survey showed that Indonesian 15-year-old students' science achievement was still lower than that of OECD countries. This study aims to explore factors related to students' science achievement at the student and school levels in Indonesia. Although it dates to 10 years, we use the PISA 2015 datasets since it is focused on science and includes several variables that are not available in either PISA 2018 or 2022. We use multilevel modeling implemented in R statistical software. We find that 50.9% of the total variance in students' science achievement is attributable to differences among students (level 1), while the remaining variance is associated with school differences (level 2). In addition, the random-slope model outperformed the random-intercept and null models. Student-level variables significantly influencing students' science achievement are gender, the socioeconomic and cultural status index, science enjoyment, self-efficacy, and epistemological beliefs about science. Meanwhile, school-level variables significant for students' science ability include school type and the disciplinary climate in science classes. Further improvements and studies are needed to increase Indonesian students' science achievement in PISA 2025.